Anca negative pauci-immune crescentic glomerulonephritis and mixed connective tissue disease: a case study - Fernandes,Sara (2020)
Abstract One of the most common causes of rapidly progressive glomerulonephritis (RPGN) is pauci-immune crescentic glomerulonephritis (CrGN). In the majority of cases, this condition has a positive serologic marker, the anti-neutrophil cytoplasmic antibodies (ANCAs), but in approximately 10% there are no circulating ANCAs, and this subgroup has been known as the ANCA-negative pauci-immune CrGN. RPGN can be associated with systemic diseases, but there are only few case reports describing the association with mixed connective tissue disease (MCTD). The authors report a case of ANCA-negative CrGN associated with a MCTD.